Glycemic lability index and mortality in critically ill patients—A multicenter cohort study. Issue 9 (20th May 2021) - Hanna, Michel; Balintescu, Anca; Glassford, Neil; Lipcsey, Miklos; Eastwood, Glenn; Oldner, Anders; Bellomo, Rinaldo; Mårtensson, Johan
Abstract: Background: Emerging evidence indicates a relationship between glycemic variability during intensive care unit (ICU) admission and death. We assessed whether mean glucose, hypoglycemia occurrence, or premorbid glycemic control modified this relationship. Methods: In this retrospective, multicenter cohort study, we included adult patients admitted to five ICUs in Australia and Sweden with available preadmission glycated hemoglobin A1c (HbA1c) and three or more glucose readings. We calculated the glycemic lability index (GLI), a measure of glycemic variability, and the time‐weighted average blood glucose (TWA‐BG) from all glucose readings. We used logistic regression analysis with adjustment for hypoglycemia and admission characteristics to assess the independent association of GLI (above vs. below cohort median) and TWA‐BG (above vs. below cohort median) with hospital mortality. Results: Among 2305 patients, 859 (37%) had diabetes, median GLI was 40 [mmol/L] 2 /h/week, median TWA‐BG was 8.2 mmol/L, 171 (7%) developed hypoglycemia, and 371 (16%) died. The adjusted odds ratio for death was 1.61 (95% CI, 1.19‐2.15; P = .002) for GLI above versus below median and 1.06 (95% CI, 0.80‐1.41; P = .67) for TWA‐BG above versus below median. The relationship between GLI and mortality was not modified by TWA‐BG ( P [interaction] = 0.66), a history of diabetes ( P [interaction] = 0.89) or by HbA1c ≥52 mmol/mol (vs. <52 mmol/mol) ( P [interaction] = 0.29). Conclusion: In adult patients admitted to an ICU in Sweden and Australia, a high GLI was associated with increased hospital mortality irrespective of the level of mean glycemia, hypoglycemia occurrence, or premorbid glycemic control. These findings support the assessment of interventions to reduce glycemic variability during critical illness.